2013
DOI: 10.1007/s00134-013-3109-3
|View full text |Cite
|
Sign up to set email alerts
|

A research agenda on the management of intra-abdominal candidiasis: results from a consensus of multinational experts

Abstract: Specific recommendations were elaborated on IAC management based on the best direct and indirect evidence and on the expertise of a multinational panel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
138
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(155 citation statements)
references
References 77 publications
6
138
0
11
Order By: Relevance
“…Despite the lack of randomized trials, antifungal therapy for patients with severe community-acquired or healthcare-associated intra-abdominal infection is recommended if Candida is grown from cultures [9,84].…”
Section: What Are Remaining Areas Of Uncertainty? Invasive Candidiasismentioning
confidence: 99%
“…Despite the lack of randomized trials, antifungal therapy for patients with severe community-acquired or healthcare-associated intra-abdominal infection is recommended if Candida is grown from cultures [9,84].…”
Section: What Are Remaining Areas Of Uncertainty? Invasive Candidiasismentioning
confidence: 99%
“…Recently, a consensus of multinational experts proposed enhanced recommendations for the management of IAC [7]. Using these criteria, Bassetti et al, in an article recently published in Intensive Care Medicine, reported a retrospective international cohort of 481 patients treated for IAC [8].…”
mentioning
confidence: 99%
“…Due to the diversity of clinical manifestations of IAC, future investigators should seek for homogenous populations to more closely address the diagnosis and therapeutic issues of these complex cases. The framework of the multinational consensus brings the opportunity for better definitions and enhanced inclusion/ exclusion criteria [7]. Some specific sub-categories of patients at high risk of IAC could be identified in future trials, illustrated in Table 1.…”
mentioning
confidence: 99%
“…In their article published in the current issue of Intensive Care Medicine, Bassetti et al [6] propose specific recommendations from a consensus of experts. This laudable attempt is a first and welcome step but, as expected, it also highlights the moderate or low quality of evidence in many fields.…”
mentioning
confidence: 99%
“…A large part of the common confusion lies in these different clinical situations, as they complicate the decision-making process of the experts in coming to a consensus regarding the diagnosis and treatment. To improve readability and prioritization of the long list of recommendations provided by Bassetti et al [6], we would like to emphasize several points which may help clinicians identify early those surgical patients who truly would benefit from treatment with.…”
mentioning
confidence: 99%